Implementasi Biaya Pendidikan di Pondok Pesantren Daarut Tauhid - Cucu Munawaroh; Ilham Agustian Widia Yusuf; G. Ginanjar Masruri; Badrudin; Qiqi Yuliati Zakiah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the implementation of education costs at the Daarut Tauhiid Islamic Boarding School by examining financing policies, budget planning, implementation and use of funds, financial organization, supervision and its contribution to the quality of education. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that the Islamic boarding school financing policy is based on sharia principles, accountability, and participation. Budget planning is carried out systematically through identification of needs, analysis of funding sources, and determination of program priorities. The implementation of the use of funds is carried out according to plan, with transparent and flexible recording of the dynamics of needs. The organization of funds is carried out through a clear and professional structure, while supervision is carried out periodically through internal and external audits. Financing support has been proven to contribute to improving the quality of education through improving facilities and infrastructure, improving teacher welfare, and strengthening the character education program for students. This study recommends increasing public participation in financial supervision and diversifying financing sources through productive waqf and Islamic boarding school business units.